A produção do conhecimento no Serviço Social dos cursos presenciais das faculdades privadas de João Pessoa/PB - Cavalcante, Deise Moreira (2022)
This Academic Master's Thesis is entitled THE PRODUCTION OF KNOWLEDGE IN SOCIAL SERVICE IN THE PRIVATE FACULTIES OF JOÃO PESSOA, PB, and its object of study is the production of knowledge in Social Service promoted in undergraduate courses in Social Service in private institutions of higher education in João Pessoa, Paraíba. With this purpose, the investigative studies focus on the analysis of the process of production of knowledge generated at the level of undergraduate courses in Social Work in private educational institutions in line with the analysis of two categories: the neoliberal impacts on the privatization of higher education and the neoconservative influxes that occurred from the post-modern offensive. Regarding methodology, it is classified as a bibliographic and documentary research using the state of the art of the productions of the Course Completion Works, whose object of analysis is related to the Theoretical-Practical Foundations of Social Service, elaborated by the students in the period from 2016 to 2020. The state-of-the-art methodology is operationalized through the adoption of bibliographic indicators, which are: areas of knowledge, themes and referenced authors. As for the method, the research is based on the dialectical historical materialism method for understanding and analyzing the reality under study, through economic, historical, cultural and political determinants. As for the research material, 68 (sixty-eight) TCC, belonging to two private higher education institutions, were analyzed. Of the four private institutions of Higher Education, in the face-to-face modality, in the area of Social Service, in the city of João Pessoa/PB, which had graduating classes, the TCC of only two (IES-1 and IES-3) were selected: because the IES-2 TCC did not meet the parameters established in the research; and the TCC of IES-4 were not configured as monographic works, but articles. Conclusively, the analysis of the results regarding the state of the art of the Course Conclusion Papers indicates the incidence of neoconservative tendencies that reinforce the immediatist, repetitive, fragmented and moralistic professional practice, marked by neopositivist and postmodern traits. The analytical focus of the TCC around the Theoretical-Practical Foundation of Social Work points to a training process in the private sphere linked to profitability, inferring to the students a technicist perception of the profession. Certainly, the possibility of massification of these contents expressed in the elaboration of the TCC of students graduated from private institutions marks the creation of a neoconservative professional profile that threatens the hegemony of the critical profile of the Brazilian social worker, based on the Professional Project of Social Service, linked to the interests of the working classes, priority target of professional actions. This evidence confirms the research hypothesis that the legacy of critical-dialectical Modernity still predominates in the production of knowledge of the Brazilian Social Work, however the analytical findings of this research reveal that the alternative of facing the crisis of capitalism influences modern critical thinking through neoconservative postmodern influxes that permeate the production of knowledge in the Bachelor's Degree Courses in Social Work at private higher education institutions in João Pessoa/PB.